Battlefield Acoustics - Damarla, Thyagaraju (Springer, 2016)
This book presents all aspects of situational awareness using acoustic signals. It starts by presenting the science behind understanding and interpretation of sound signals. The book then goes on to provide various signal processing techniques used in acoustics to find the direction of sound source, localize gunfire, track vehicles and detect people. The necessary mathematical background and various classification and fusion techniques are presented. The book contains majority of the things one would need to process acoustic signals for all aspects of situational awareness in one location. The book also presents array theory, which is pivotal in finding the direction of arrival of acoustic signals. In addition, the book presents techniques to fuse the information from multiple homogeneous/heterogeneous sensors for better detection. MATLAB code is provided for majority of the real application, which is a valuable resource in not only understanding the theory but readers can also use the code as a spring-board to develop their own application based software code.